Examining the Relationship between Online Store Atmosphere, Perceived Interactivity, Flow Experience and Purchase Intention in Electronic Commerce: A Research within the Stimulus-Organism-Response (S-O-R) Paradigm - Güleç, Utku Tevfik; Ünüsan, Çağatay (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The upward trend towards e-commerce is perceived through the booming e-commerce volume worldwide. At this point, it is crucial to know the factors affecting consumers’ intentions to purchase. This research aims to determine the role of online store atmosphere, perceived interactivity, and flow experience on purchase intention using the Stimulus-Organism-Response (S-O-R) theory. For this purpose, empirical data were obtained through an online questionnaire from 437 consumers who had priorly shopped from e-commerce sites. Partial least squares structural equation modeling (PLS-SEM) was used to validate the relationships proposed in the research model. The results have revealed that visual cues positively affect purchase intention through the flow experience; perceived personalization positively influences purchase intention through the flow experience. These results provide a better understanding of purchase intention. Thus, it contributes to online store managers and e-commerce researchers.